2016
DOI: 10.1080/01616412.2016.1177929
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state functional magnetic resonance imaging in patients with leukoaraiosis-associated subcortical vascular cognitive impairment: a cross-sectional study

Abstract: The present study provides neuroimaging evidence for the recognition of LA-associated SVCI. Moreover, the differences in the functional alterations of the resting-state DMN might be a distinguishing feature between SVCI and amnestic mild cognitive impairment patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Many studies have shown ( 58 61 ) that FC abnormalities in VCI subjects are closely related to CI ( Figure 1 ). DMN is the key brain region for post-stroke CI.…”
Section: Application Of Rs-fmri In the Vci Studymentioning
confidence: 99%
“…Many studies have shown ( 58 61 ) that FC abnormalities in VCI subjects are closely related to CI ( Figure 1 ). DMN is the key brain region for post-stroke CI.…”
Section: Application Of Rs-fmri In the Vci Studymentioning
confidence: 99%
“…Cognitive impairment, the most common clinical feature associated with ILA, manifests as deficits in thinking ability, memory, executive function, and attention ability (Sultzer et al, 1995 ; Li et al, 2017 ). Previous studies have suggested that normal elderly individuals with ILA are at high-risk of further cognitive decline, and the magnitude of the ILA is positively correlated with the severity of cognitive deficits (Ross et al, 2005 ; Te et al, 2015 ; Chen et al, 2016 ). However, the neurobiological pathway underlying cognitive impairment in ILA has not been well illuminated.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging studies on ILA have demonstrated white matter (WM) changes, especially in the fronto-subcortical circuits (Viana-Baptista et al, 2008 ; Yuan et al, 2017 ). Additionally, evidence from functional brain connectome studies on ILA has further shown the involvement of the dysfunction of several networks in ILA, including the default mode network, frontoparietal network, dorsal attention network, salience network and corticostriatal network (Chen et al, 2016 , 2019 ; Liu et al, 2019a , b ). These studies have suggested that “brain network dysfunction” may be the best explanatory model for illuminating the neurobiological pathway underlying cognitive impairment in ILA.…”
Section: Introductionmentioning
confidence: 99%
“…The default-mode network (DMN) is closely related to selective extraction and classification of episodic memory and self-cognition, and it plays an important role in cognitive function [17]. Patients with LA-associated subcortical vascular cognitive impairment (SVCI) exhibited significant differences in the functional alterations of the DMN, which might be a feature distinguishing between SVCI and amnestic mild cognitive impairment (aMCI) patients [18]. As for the sensorimotor network (SMN), patients with LA also have impaired sensorimotor integration caused by interfering with the communication or coordination of these aforementioned regions related to the SMN [19].…”
Section: Resting-state Fmri(rs-fmri)mentioning
confidence: 99%